2022
DOI: 10.1002/jmv.28126
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and reliable inactivation protocols for the diagnostics of emerging viruses: The example of SARS‐CoV‐2 and monkeypox virus

Abstract: The emergence and sustained transmission of novel pathogens are exerting an increasing demand on the diagnostics sector worldwide, as seen with the ongoing severe acute respiratory coronavirus 2 (SARS‐CoV‐2) pandemic and the more recent public health concern of monkeypox virus (MPXV) since May 2022. Appropriate and reliable viral inactivation measures are needed to ensure the safety of personnel handling these infectious samples. In the present study, seven commercialized diagnosis buffers, heat (56°C and 60°C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The results showed that the MPXV DNA was stable over 5 days of storage with no significant drop in Ct values observed, even when the DNA aliquot was exposed to temperatures above 30 °C for several hours on day 3. This stability is consistent with the results of other studies (97,99). In addition, the DNA stability after MPXV inactivation using an autoclave (121 °C, 30 min) was investigated.…”
Section: Mpxv Inactivationsupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that the MPXV DNA was stable over 5 days of storage with no significant drop in Ct values observed, even when the DNA aliquot was exposed to temperatures above 30 °C for several hours on day 3. This stability is consistent with the results of other studies (97,99). In addition, the DNA stability after MPXV inactivation using an autoclave (121 °C, 30 min) was investigated.…”
Section: Mpxv Inactivationsupporting
confidence: 90%
“…In addition, evaluations of commonly used reagents in clinical laboratories such as Trizol and commercially available lysis buffer AVL with ethanol were performed, showing inactivation of MPXV after a 10-minute incubation at room temperature (98). A study testing seven commercial diagnostic buffers confirmed inactivation of MPXV at different incubation times, and heat (56 °C and 60 °C) and sodium dodecyl sulfate detergent were also found to be effective, highlighting the importance of matching the protocol to downstream biological processes (99).…”
Section: Mpxv Inactivationmentioning
confidence: 99%
“…This was consistent with the conditions recommended in many guidelines. This effective inactivation condition requires higher requirements, compared to reports that MPXV can effectively inactivate at 56 °C for 10 min (titer reduction > 6.9 lg TCID 50 /mL) [ 31 ]. Some studies have also shown that MPXV can be inactivated at 70 °C for less than 5 min, which is less than the required 10 min in this study [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there are many studies or guidelines describing specific protocols for chemical or physical inactivation of viruses. In practice, this regulatory framework does not harmonize practices or guarantee their effectiveness as demonstrated by recent viral outbreaks and the need for systematically published new protocols to protect laboratory workers ( Quéromès et al, 2023 ).…”
Section: Ways For Future Improvementmentioning
confidence: 99%